Public Relations Approach In Building Client Trust In Cleaning Service Outsourcing At Pt Zara Nusantara Utama - Jeanni Betasya Sabila; Martha Heriniazwi Dianthi; Dilmai Putra (Jurnal Multidisiplin, 2026)
This study aims to analyze the public relations approach in building client trust in cleaning service outsourcing at PT Zara Nusantara Utama. This research uses a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observations, and documentation. The research informants consisted of public relations staff, company clients, and operational employees involved in service activities. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results show that the public relations approach in building client trust is carried out through responsive communication, open handling of client complaints, and efforts to maintain cooperative relationships with clients. Based on the Relationship Management Theory, the relationship between the company and clients is reflected through five main dimensions: trust, openness, commitment, mutual control, and satisfaction. Client trust has been established, although it is still influenced by the consistency of service quality in the field. Communication openness and company commitment are demonstrated through responses to client complaints, although they tend to be reactive. The level of client satisfaction is categorized as fairly satisfied since the services help operational needs despite some inconsistencies in service delivery. This study indicates that the success of building client trust is determined not only by technical service quality but also by effective communication and sustainable relationship management between the company and its clients.